2004
DOI: 10.2527/2004.82102978x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary fish oil supplementation on exercising horses

Abstract: Ten horses of Thoroughbred or Standardbred breeding were used to study the effects of dietary fish oil supplementation on the metabolic response to a high-intensity incremental exercise test. Horses were assigned to either a fish oil (n = 6) or corn oil (n = 4) treatment. The fish oil (Omega Protein, Hammond, LA) contained 10.6% eicosapentaenoic acid and 8% docosahexaenoic acid. Each horse received timothy hay and a textured concentrate at a rate necessary to meet its energy needs. The supplemental oil was top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
3
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 20 publications
4
36
3
1
Order By: Relevance
“…The training program failed to induce the need for an anaerobic energy supply, and this could also explain the lack of differences in plasma lactate level between fat and starch treatments (Figure 1). A similar conclusion was reached using corn and fish oil supplementation (O'Connor et al 2001). Ultimately, it seems that horses around the age of 7 years and having good fitness express a high activity of lactate clearance to prevent the formation of significant peaks of this metabolite in plasma.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…The training program failed to induce the need for an anaerobic energy supply, and this could also explain the lack of differences in plasma lactate level between fat and starch treatments (Figure 1). A similar conclusion was reached using corn and fish oil supplementation (O'Connor et al 2001). Ultimately, it seems that horses around the age of 7 years and having good fitness express a high activity of lactate clearance to prevent the formation of significant peaks of this metabolite in plasma.…”
Section: Resultssupporting
confidence: 59%
“…The quality (fatty acid composition) of the dietary fat source also modifies the glucose metabolism. Fish oil supplementation resulted in lower glucose levels compared to the corn oil fed group (O'Connor et al 2001). As none of the above mentioned experiments applied to sunflower oil treatment of our study, we can only speculate that the plasma glucose lowering effect may depend on the fatty acid composition of the dietary fat.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Demaison, Blet, Sergiel, Gregoire, and Argaud (2000) found that rats consuming fish oil had reduced heart rate, aortic flow, and cardiac output due to a decrease in vascular resistance. Similarly, O'Connor et al (2004) found that thoroughbred horses administered fish oil for 63 days had lower heart rates and packed-cell volume during exercise than horses fed corn oil.…”
Section: Omega-3 Fatty Acids and Exercising Animals: Relevance To Hummentioning
confidence: 99%
“…A large number of both experimental and epidemiological studies have since been conducted to examine the effect of consuming fish oil, which contains high amounts of EPA and DHA, on cardiovascular health, with most showing an inverse correlation on morbidity and mortality (Albert et al, 2002;Hu et al, 2002;Lemaitre et al, 2003;Oomen et al, 2000;Rissanen, Voutilainen, Nyyssonen, Lakka, & Salonen, 2000;von Schacky, Angerer, Kothny, Theisen, & Mudra, 1999). The cardioprotective effects of omega-3 fatty acids are ascribed to improvements in various cardiovascular risk factors including a reduction in blood-platelet aggregation (Mori, Beilin, Burke, Morris, & Ritchie, 1997;Phang, Sinclair, Linez, & Garg, 2012), decreased inflammation (Heller, Koch, Schmeck, & van Ackern, 1998;Zhao et al, 2004), enhanced endothelial function (Fleischhauer, Yan & Fischell, 1993), positive changes in blood lipids (Calabresi et al, 2004;Harris, 1989;Herrmann, Biermann, & Kostner, 1995), and decreased blood pressure (Paschos, Magkos, Panagiotakos, Votteas, & Zampelas, 2007;Prasad, 2009).…”
mentioning
confidence: 99%